Kepribadian Ayub - Stevanus, Kalis (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
Individual personality development is influenced by various factors, there are internal factors and external factors. This paper aims to determine whether a unique life experience, namely suffering, can influence the formation of a person's personality. This study uses a biblical study approach to the story of Job in the book of Ayub with a narrative interpretation method and also uses a literature study approach. It is evident that unpleasant life experiences such as the suffering that befell Job do not change Job's good personality. Job was a godly and honest man; fear Allah and shun evil; a person of sincerity or integrity; an optimist; a generous person; and a man who is loyal to his wife